2022
DOI: 10.26434/chemrxiv-2022-0g593
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanoscale porosity in microellipsoids cloaks interparticle capillary attraction at fluid interfaces

Abstract: Anisotropic particles pinned at fluid interfaces tend towards disordered multi-particle configurations due to large, orientationally-dependent, capillary forces, which is a significant barrier to exploiting these particles to create novel functional self-assembled materials. Therefore, current interfacial assembly methods typically focus on isotropic spheres, which have minimal capillary attraction and no dependence on orientation in the plane of the interface. In order to create long-range ordered structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…17,112,113 Therefore, CEC efficiency is also anticipated to be affected by the surface roughness of catalytic nanoparticles, e.g., raspberry-like, patchy, and/or hollow nanoparticles. More remarkably, a recent study showcased that the nanoscale porosity on particle surfaces can effectively prevent undesired particle agglomeration upon ultrasonication 114,115 (Figure 8e). Improving particle dispersity is helpful to expose more surface area for liquid−solid CE.…”
Section: Enhancement Pathway For Cecmentioning
confidence: 89%
“…17,112,113 Therefore, CEC efficiency is also anticipated to be affected by the surface roughness of catalytic nanoparticles, e.g., raspberry-like, patchy, and/or hollow nanoparticles. More remarkably, a recent study showcased that the nanoscale porosity on particle surfaces can effectively prevent undesired particle agglomeration upon ultrasonication 114,115 (Figure 8e). Improving particle dispersity is helpful to expose more surface area for liquid−solid CE.…”
Section: Enhancement Pathway For Cecmentioning
confidence: 89%
“…1−4 Among various interparticle interactions between colloids at the interface that contribute to collective interfacial microstructure and properties, attractive capillary interactions are significant and originate from curved menisci around the particle. 5 In particular, far-field quadrupolar interfacial deformation 6,7 results from introducing either particle surface roughness in otherwise smooth spheres 5 or shape anisotropy as in ellipsoids. 8 The former originates from nanoscale random undulations in the contact line, which decays to a quadrupolar curved menisci, while the latter is a consequence of Young's law requiring constant three-phase contact angle around an object with varying curvature.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The existence of a slip plane separating high and low shear rate zones was an indicator that the shear thinning behavior stems from yielding of the particle layer at the interface (Barman and Christopher 2014). Shape anisotropic particles have also been studied at air-water interfaces (Beltramo et al 2017;Bertsch et al 2018;Trevenen et al 2022). Beltramo et al (2017) demonstrated a significant yield stress in interfacial networks of shape anisotropic particles (polystyrene ellipsoids 2.48-μm long and 0.45-μm wide), much higher than for spherical particles at the same interfacial coverage (Beltramo et al 2017).…”
Section: Introductionmentioning
confidence: 99%